Soluble extracellular matrix metalloproteinase inducer (EMMPRIN, EMN) regulates cancer‐related cellular functions by homotypic interactions with surface CD147. (11th September 2015) - Knutti, Nadine; Kuepper, Michael; Friedrich, Karlheinz
Abstract : EMMPRIN (extracellular matrix metalloproteinase inducer) is a widely expressed glycoprotein and a member of the immunoglobulin superfamily which exists in both a membrane‐spanning and a soluble form. Homotypic interactions of EMMPRIN underlie its multiple roles in normal development and pathological situations such as viral infections, Alzheimer's disease and cancer. This study employed a recombinant soluble, fully glycosylated EMMPRIN domain (rhsEMN) as a tool to characterize the structural basis of EMMPRIN‐EMMPRIN receptor (EMNR) contacts and their functional effects on MCF‐7 breast carcinoma cells. rhsEMN did not form dimers in solution but bound to surface EMMPRIN (EMN) on MCF‐7 cells with high affinity and was readily internalized. The interaction interface for the homotypic contact was localized to the N‐terminal Ig domain. rhsEMN exerted a stimulatory effect on proliferation of MCF‐7 cells whereas it reduced cell migration in a dose‐dependent manner. These effects were accompanied by an upregulation of endogenous EMMPRIN as well as of matrix metalloproteinase‐14 (MMP‐14), a membrane‐bound protease involved in the extracellular release of soluble EMMPRIN, indicating a regulatory feedback mechanism. The proliferation‐promoting activity of rhsEMN was mimicked by a novel functional antibody directed to EMMPRIN, underscoring that crosslinking of cell surface EMMPRIN (EMNR) is crucial for eliciting intracellular signalling. Addressing malignancy‐related signal transduction in HEK‐293 cells, we could show that rhsEMN triggers the oncogenic Wnt pathway. Abstract : Effects of rhsEMN, a soluble domain of membrane‐spanning EMMPRIN (Extracellular matrix metalloproteinase inducer) on breast cancer cells were studied. Soluble EMN homotypically contacts cell surface EMMPRIN and thereby triggers cancer‐related cellular responses such as cell proliferation and activity of the oncogenic Wnt pathway. Moreover, it probably drives positive regulatory feedback by upregulating EMMPRIN expression and release.